The Great Lakes Urban Coastal Observing System (GLUCOS): Results of First Deployments in Coastal Lake Michigan - Consi, T.R.; Barske, G.; Bootsma, H.; Hansen, T.; Janssen, J.; Kipp, J.; Klump, V.; Paddock, R.; Szmania, D.; Waples, J.T. (OCEANS 2007, 2007)
The UWM Great Lakes WATER Institute is developing an underwater observatory designed for scientific studies of physical, chemical and biological processes in Lake Michigan and similar large lakes. GLUCOS, the Great Lakes Urban Coastal Observing System, is a buoy-based sensor network that will support research on the interactions between Milwaukee Harbor and the lake, and other processes in coastal Lake Michigan. The initial system configuration will consist of two large (Endurance) buoys designed to be deployed in fixed positions to gather long (up to 1 year) time series of data, and five smaller (Pioneer) buoys designed for rapid deployment over shorter periods of time (up to 2 months). The more transportable Pioneer buoys can be easily deployed in different array geometries to support changing scientific requirements in a single field season. The Pioneer buoy components of GLUCOS have been built and field tested, both individually and as a multi- buoy array in Lake Michigan near Milwaukee Harbor. The current design of the Pioneer buoys and the results of the Pioneer field tests are the subjects of this paper.